Player acceptance of human computation games - Wang, Xiaohui (2018)
Harnessing human power to perform computational tasks through gameplay, known as Human Computation Games (HCGs), has been increasingly popular. Their usefulness has also been documented in literature. Despite the potential of HCGs, understanding of the HCG acceptance is still incomplete. Many HCGs did not survive the initial deployment phase because few players use them. This could be primarily improved by examining the driving factors behind HCG acceptance based on a customized theoretical framework. To address the research gap, two main research questions are identified: 1) what are the underlying factors driving HCG acceptance, and 2) how the influences of these driving factors generalize across contexts and time. This doctoral thesis consists of three interrelated studies designed to understand the acceptance of HCGs. This research project begins by proposing an extended technology acceptance model (extended TAM) that incorporates aesthetic experience and output quality to predict player acceptance of HCGs. The extended TAM theorizes that perceived ease of use and perceived output quality are the external variables of perceived usefulness and perceived aesthetic experience, which in turn affect the attitude and intention to play HCGs. Study I addressed the first research question. Kpoprally, a music video tagging game, was first developed. Data was collected with a survey where 132 participants evaluated Kpoprally. Results identified all the perception factors as salient predictors of HCG acceptance. Among them, perceived aesthetic experience was demonstrated as the strongest predictor of attitude and intention, and perceived usefulness was significantly associated with attitude only, suggesting that psychological rather than technical factors are more important in predicting players’ preferences and intentions. Study II was conducted to compare the perceptions and acceptance of HCGs to those of non-game human computation systems (HCSs) and examine the effect of aesthetic experience on acceptance with experiment. A between-subjects experiment was carried out, in which 95 participants were randomly assigned to test an HCG and an HCS respectively. The results of Study II provided experimental evidence for the effect of aesthetic experience on acceptance. Regression analyses explaining the acceptance of the HCG and the HCS were conducted separately. Aesthetic experience, usability, and output quality played a different role in predicting the acceptance of the HCG and the HCS, indicating that acceptance of the HCG and the HCS should be treated differently. Finally, Study III was conducted to investigate the HCG acceptance in the mobile context and with continuous use. A longitudinal survey study was conducted with participants using a mobile version of Kpoprally within a two-week period. Individuals’ perceptions and acceptance were measured at the three different time points. Results of a pooled-sample structural equation modeling showed that the extended TAM was supported in the mobile context. Moreover, this study also demonstrated that different predictors come into play in different stages of usage. Perceived aesthetic experience was a consistently important predictor of HCG acceptance, while the effect of perceived ease of use and perceived usefulness were time-dependent. Therefore, investigating the continuance use of HCGs with longitudinal data is necessary to capture a full image of user acceptance. By combining the findings in Study I, II, and III, this research presents a comprehensive understanding of HCG acceptance in different platforms and across time. Results of this research highlight the role of aesthetic experience, output quality, ease of use, usefulness in HCG acceptance, providing guidance for researchers in HCG evaluation. In terms of practical implications, finding of this research may facilitate the understanding of user requirements and lead to the development of more successful HCGs that are attractive to target audiences.